2012
DOI: 10.1021/ma300362f
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivities of Block Copolymer Electrolytes with Various Conducting Pathways: Sample Preparation and Processing Considerations

Abstract: We explored the relationship between ionic conductivities and morphology in a lithium perchlorate-doped poly(styrene-b-ethylene oxide) (PS−PEO) system using ac impedance spectroscopy, in situ small-angle X-ray scattering, and transmission electron microscopy. To aid in morphological analysis, a flow alignment technique was used to orient nanoscale domains in order to facilitate characterization of nanostructures such as hexagonally perforated lamellae (HPL), hexagonally packed cylinders (HEX), and lamellae (LA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(177 citation statements)
references
References 56 publications
2
173
0
2
Order By: Relevance
“…The deviation between SAXS and TEM results likely was due to POEM shrinkage under exposure to the electron beam in TEM. 16,50 With the addition of LiCF 3 SO 3 at the salt-doping ratio of [EO] : [Li] ¼ 15 : 1, the primary peak of P(S-OEM) shied to q* ¼ 0.018Å À1 , giving a domain spacing of 34.4 nm. The scattering peaks located at q/q* ¼ 1, O3, 2, O7, and 3 suggest a hexagonally-packed cylinder (HEX) morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The deviation between SAXS and TEM results likely was due to POEM shrinkage under exposure to the electron beam in TEM. 16,50 With the addition of LiCF 3 SO 3 at the salt-doping ratio of [EO] : [Li] ¼ 15 : 1, the primary peak of P(S-OEM) shied to q* ¼ 0.018Å À1 , giving a domain spacing of 34.4 nm. The scattering peaks located at q/q* ¼ 1, O3, 2, O7, and 3 suggest a hexagonally-packed cylinder (HEX) morphology.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these two blocks could form unique patterns with special pathways to increase ionic conductivities. [55] With these improvements, the ionic conductivity of dual-ion GPEs had reached over 10 −3 S cm −1 , [56][57][58] with the tensile strength over 10 MPa [59,60] and the thermal stability over 400 °C. [61] Recently, some other effective strategies have been further reported by immobilizing anions to realize single lithium-ion conducting GPEs or directly introducing redox-active mediators into GPEs.…”
Section: The Performance Improvement Of the Gpesmentioning
confidence: 99%
“…68 In anhydrous ion transport materials, it has been shown that 3-D continuous ionic domains can provide higher conductivity values than 1-D or 2-D channels. 69,70 In water-assisted ion transport materials, experimental comparisons have been conducted on the minor phases in spherical and cylindrical morphologies, together with lamellae, while the matrices of cylindrical and spherical phases were scarcely investigated. This was likely due to the fact that the formation of matrices require a high volume fraction of the ionic block and can lead to excessive hydration and loss of mechanical integrity upon water sorption.…”
Section: ■ Introductionmentioning
confidence: 99%